Influences of Presentation about Smoking Effect Toward Teenagers Knowledge In Class X at SMA Negeri 5 Palu: smoking effect - Nike Nurjanah; Sukrang; James Walean (Politeknik Karya Persada Muna, 2021)
Background: Smoking is become problem that still could not solve well till now. A lot of relus and annousment regarding smoking could not stop them, but mone tham expectation, the real faet based on Riskesdas meutioned that smoking more aggressive. The purposeof this research to obtain the influence of presentation about smoking effect toward teenager’s knowledge in grade X of SMA Neg 5 palu. Method: This is qualitative research. Actualy quantitative approached used for inferential research (hypothesis test) to analys the data numerical data that formulated in statistic method. Sampling number was 31 teenager that taken by cluster sampling tehnique Results: of research shown that performanc of personal hygiene about 51,4%, bivariate analys of wilcoxon tes with asymp. Sig (ztailed) value : 0,000. (0,000<0,05). So, it concluded that there is influence of presentation about smoking effect toward teenager’s knowledge in grade X of SMA Neg 5 palu Conclusions: this research mentioned there is differences of pre test and post tes studi result, that means there is influence of presentation about smoking effect toward teenager’s knowledge in grade X of SMA Neg 5 palu Keywords: Smoking effect, Teenager’s knowledge